Usability Sistem Informasi Aparatur Sipil Negara (SIASN) Menggunakan Metode System Usability Scale (SUS) pada BKPSDM Kabupaten Gorontalo - Arifin Ahudulu; Alter Lasarudin; Frangky Tupamahu; Hilmansyah Gani (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
The acceleration of digital transformation in the public sector requires reliable personnel information systems to support efficient and integrated administrative services. The State Civil Apparatus Information System (SIASN) serves as a national platform for managing personnel data and administrative processes of civil servants in Indonesia. However, its implementation at the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Gorontalo Regency still faces several technical and usability-related challenges that may affect user experience and service effectiveness. This study aims to identify user constraints, measure the usability level of SIASN, and provide recommendations for system improvement. A quantitative descriptive approach was employed through data collection using questionnaires, in-depth interviews, and field observations. The study involved 30 active SIASN users, and usability data were analyzed using the System Usability Scale (SUS) instrument. The results indicate that the main obstacles experienced by users include data storage failures, slow system access during peak hours, data updates that have not taken place in real-time, complexity of menu navigation, and limitations of account recovery features. The results of the usability measurement resulted in an average SUS score of 76.4 which is included in the Good category with an Acceptable acceptance rate. These findings show that SIASN is able to support personnel administration activities well and is accepted by users. However, improving the quality of the system is still necessary through optimizing server performance, simplifying the user interface, synchronizing data in real-time, and developing a password reset feature independently. The results of this research are expected to be evaluation materials for developers to improve the quality of digital-based personnel services.